Immobilization of Pb2+ and Cr3+ using bentonite-sulfoaluminate cement composites. (20th November 2019) - Niu, Mengdie; Li, Guoxin; Wang, Yan; Cao, Li; Han, Lulu; Li, Qiqi; Song, Zhanping
Highlights: Bent-CSA composites were prepared by partial replacing CSA with bentonite. Bent-CSA composites show efficient immobilization performance on Pb 2+ and Cr 3+ . The influence of Pb 2+ and Cr 3+ on the compressive strength of Bent-CSA was not significant. Abstract: The contamination of Pb and Cr to the environment cannot be ignored. It is an urgent task to explore an efficient and cheap technique to treat Pb and Cr. Bentonite-sulfoaluminate cement composites (Bent-CSA) was prepared to solidify Pb 2+ and Cr 3+, and their leachability, setting time, and compressive strength were researched in this study. Then the hydration products were analyzed via XRD and SEM. The results show that Bent-CSA immobilized Pb 2+ and Cr 3+ efficiently, the compressive strength was slightly affected by Pb 2+ and Cr 3+, but that gradually decreased as bentonite content increased. Bent-CSA could be reused as foundation cushion and roadbed materials after solidifying Pb 2+ and Cr 3+ .